Differential association of abdominal, liver, and epicardial adiposity with anthropometry, diabetes, and cardiac remodeling in Asians - Lee, Vivian; Han, Yiying; Toh, Desiree-Faye; Bryant, Jennifer A.; Boubertakh, Redha; Le, Thu-Thao; Chin, Calvin W. L. (Frontiers in Endocrinology, 2024)
Background: Heterogenous deposition and homeostasis roles of physiologic and ectopic adipose tissues underscore the implication of fat compartmentalization on cardiometabolic risk. We aimed to characterize the distribution of abdominal visceral adipose tissue (VAT), subcutaneous adipose tissue (SAT), epicardial adipose tissue (EAT) and liver fat on magnetic resonance imaging (MRI), and evaluate their associations with anthropometric indices and adverse cardiac remodeling.In this cross-sectional observational study, 149 Asian adults (57.0±12.8 years; 65% males) with at least one cardiometabolic risk factor underwent multiparametric fat and cardiovascular MRI. Anthropometric indices included body mass index (BMI), waist circumference (WC), waist-hip ratio (WHR) and bioimpedance body fat mass (BFM). Associations between fat depots and anthropometric measures as well as cardiac remodeling features were examined as a single cohort and stratified by type 2 diabetes mellitus (T2DM) status.Results: VAT and SAT had opposing associations with liver fat and EAT, therefore the VAT/SAT ratio was explored as an integrated marker of visceral adiposity. VAT/SAT was positively associated with EAT (β=0.35, P<0.001) and liver fat (β=0.32, P=0.002) independent of confounders. Of the anthropometric measurements assessed, only WHR was independently associated with VAT/SAT (β=0.16, P=0.03). Individuals with T2DM had higher VAT and lower SAT compared to those without T2DM, translating to a significantly higher VAT/SAT ratio. EAT volume was independently associated with adverse features of cardiac remodeling: increased left ventricular (LV) mass (β=0.24, P=0.005), larger myocyte volume (β=0.25, P=0.002), increased myocardial fibrosis (β=0.19, P=0.032), higher concentricity (β=0.18, P=0.035) and elevated wall stress (β=-0.18, P=0.023).Conclusions: Multiparametric MRI revealed abdominal VAT and SAT have differential associations with anthropometric indices and ectopic fats in a single cohort of Asians at risk of cardiometabolic disease. People with T2DM have expanded VAT and diminished SAT, endorsing the VAT/SAT ratio beyond usual anthropometric measurements as a marker for multiorgan visceral fat composition. Among the fat depots examined, EAT is uniquely associated with adverse cardiac remodeling, suggesting its distinctive cardiometabolic properties and implications.